Stress relaxation of PVC-O pipes at the device for manufacturing PVC-O pipes - Найда, Андрій Михайлович (Technology audit and production reserves, 2015)
PVC-O pipes are the best solution for use in water supply networks operating under high and medium pressure, irrigation systems, fire suppression systems and pump systems, as well as in other areas. So we should create a equipment for making such pipes with providing optimal process parameters. Established equipment receipt of polyvinyl chloride pipe, consists of: - Device-drawn tubes; - A device for forming a second outer diameter; - External calibration device diameter pipes. As a result of researches the optimal values of process parameters are made such as speed-drawn, temperature of the pipe that leads to the relaxation of stresses in the PVC-O pipe, when it made; it is determined that stress relaxation in the pipe in the production of PVC-O pipes is faster with minimal speed of haul-off, so use of vacuum bath after a conical mandrel is not necessary, but using the fact that the rate of release of pipes should be sufficient to industrial scale, of course vacuum bath should be applied. This study is useful in that project organization guided by research data can to design the minimum required equipment for the manufacture of PVC-O pipes.